Inhibitory effect of dietary curcumin on skin carcinogenesis in mice - Limtrakul P. (2014)
Laboratory animal model studies have suggested that curcumin may play an important role in inhibiting the process of carcinogenesis. Curcumin, the yellow pigment that is obtained from rhizomes of the plant Curcuma longa Linn (Family Zingiberaceae), is commonly used as a spice and food coloring agent. The present study was designed to investigate the chemopreventive action of dietary curcumin on 7,12-dimethylbenz[a]anthracene (DMBA)-initiated and 12-O-tetradecanoylphorbol-13-acetate (TPA)-promoted skin tumor formation in male Swiss ablino mice. At 6 weeks of age, groups of animals were fed the standard (modified AIN-76 A) diet or a diet containing 1% curcumin. At 8 weeks of age, all animals, except those in the vehicle (acetone)-treated groups, received 100 microg of DMBA dissolved in 100 microl of acetone in a single application to the skin of the back. From 1 week after DMBA application, tumor promoter (2.5 microg of TPA dissolved in 100 microl of acetone) was applied to the same areas on mouse skin twice a week for 26 weeks. All groups continued on their respective dietary regimen until the termination of the experiment. The results indicate that dietary administration of curcumin significantly inhibited the number of tumors per mouse (P < 0.05) and the tumor volume (P < 0.01). The percentage of tumor-bearing mice tended to be lower in the mice on the curcumin diet than those on the standard diet. There was no difference in growth between mice of the standard and 1% curcumin groups. The results indicate the safety and the anti-carcinogenic effect of curcumin in mice.